PENINGKATAN KAPASITAS KWT MELATI ASRI MELALUI PEMANFAATAN SISTEM SMART FARMING BERBASIS IOT DI KALURAHAN NGESTIHARJO, BANTUL - Prahenusa Wahyu Ciptadi; Marti Widya Sari; Adi Prasetyo (Jurnal Berdaya Mandiri, 2025)
This community service program aims to enhance the capacity of the Women Farmers Group (Kelompok Wanita Tani/KWT) Melati Asri in Tambak, Ngestiharjo Village, Bantul, through the implementation of smart farming innovation based on the Internet of Things (IoT). The main challenges faced by the group include limited knowledge and assistance in agricultural technology, suboptimal production management, inadequate farming facilities, and low digital literacy for marketing and product diversification. To address these issues, the program was carried out in five main stages: socialization, training, technology implementation, mentoring and evaluation, as well as sustainability planning. Training sessions covered modern agricultural technologies, organizational management, business plan development, and agricultural product diversification. Furthermore, smart farming technology, such as sensor-based monitoring systems in greenhouses, was introduced and accompanied by intensive mentoring. The outcomes show an increase in members’ knowledge of digital agriculture, skills in farm management, and awareness of innovation to strengthen local food security. The program also encouraged women’s active role in the community economy, opened wider market access through digitalization, and created opportunities for value-added agricultural product diversification. With a participatory and sustainable approach, this initiative is expected to improve productivity, efficiency, and competitiveness of KWT Melati Asri in the long term. Keywords: Smart Farming, Internet of Things, Women Farmers Group, Food Security, Community Empowerment